Implication Theme in Lemony Snickets’ A Series of Unfortunate Events "The Bad Beginning" and "The End" (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The research aims to explore the ideological perspectives of presenting the orphans through the “Us versus Them” mentality. The method of the research is mixed methods (quantitative and qualitative) research. The data is limited to (12) extracts from the selected novels, i.e., (6) from each. These extracts are derived from the two selected novels which are written by the author Daniel Handler. These novels are “The Bad Beginning” and “The End” which are derived from “Lemony Snickets' A Series of Unfortunate Events”. The analysis involves two characters: Violet is the eldest sister with 14 years old and Klaus is the middle with 12 years old. The model of van Dijk’s (2006, 2008) Socio-cognitive approach and ideological square was adopted. Violet and Klaus use the strategy of actor description to focus on the intended m using certain expressions many times to adopt their identity in the selected extracts of both novels.